Integration of Sentinel Imagery and Geographic Information System for Analysing Spatial Distribution of Senior and Vocational High School Education Facilities in West Bandung Regency, Indonesia - Hadibasyir, Hamim Zaky; Amin, Choirul; Wulandari, Retna Dwi; Maulidianti, Putri; Firdaus, Nada Salsabila (Dinasti Publisher, 2025)
Disparity in the distribution of educational facilities in developing regions is an issue to achieve equity in access to education. For example, access to senior high school (SMA) and vocational high school (SMK) has remained unequal across different sub-districts within West Bandung Regency of Indonesia and will pose a problem in attaining 12 years of compulsory education. In this research, the methods of remote sensing and GIS were integrated for analyzing the spatial distribution and accessibility to senior and vocational high school. Using data from Google Maps in 2021 and Sentinel imagery, the ANN and kernel density methods have been used in identifying the distribution pattern, while conducting buffer analysis to map coverages. In fact, there is a clustered distribution in sub-districts like Lembang, Padalarang, and Cipongkor, with isolated sub-districts like Parongpong and Rongga showing huge accessibility gaps where settlement exists over 7.5 km away from the school. These findings raise awareness of the pressing need for concerted infrastructure planning and investment at sub-national levels in pursuit of equal opportunities that are imperative for sustainable development and social equity in developing countries.